The effects of a 6-week core exercises on swimming performance of national level swimmers - Karpinski, J.; Rejdych, W.; Brzozowska, D.; Golas, A.; Sadowski, W.; Swinarew, A. S.; Stachura, A.; Gupta, S.; Stanula, A. (PLOS ONE, 2020)
The aim of this study was to assess the impact of a 6-week specialized training program aimed at strengthening core muscles to improve the effectiveness of selected elements of a swimming race on a group of Polish swimmers. Sixteen male national level swimmers (21.6 ± 2.2 years) participated in the research. The competitors were randomly assigned to 1 of 2 groups before the data collection process: an experimental (EG, n = 8) and a control (CG, n = 8) group. Both groups of swimmers underwent the same training program in the water environment (volume and intensity), while swimmers from the EG additionally performed specific core muscle training. The task of the swimmers was an individual front crawl swim of 50 m, during which the kinematic parameters of the start jump, turn and swimming techniques were recorded using a video camera system. In both groups, a minor increase in the flight phase was observed at the start (EG = 0.06 m, 1.8%; p = 0.088; CG = 0.08 m, 2.7%; p = 0.013). The time to cover a distance of 5 m after the turn and the recorded average speed in swimming this distance for the EG statistically significantly improved by 0.1 s (-28.6%; p < 0.001) and 3.56 m·s-1 (23.2%; p = 0.001), respectively. In the EG, a statistically significant improvement in 50 m front crawl swimming performance of 0.3 s (-1.2%, p = 0.001) was observed. The results of the research show that the implementation of isolated strengthening of the stabilizing muscles seems to be a valuable addition to the standard training of swimmers.